EKSISTENSI BIMBINGAN KONSELING PADA PENDIDIKAN AGAMA ISLAM DI MADRASAH ALIYAH RAUDLATUT THALABAH NGADILUWIH KEDIRI - Muslimin; Ahmad Masrukin (CENDEKIA: Jurnal Studi Keislaman, 2020)
Guidance and counseling (BK) is a process of providing targeted assistance to a person / group of people continuously and systematically by the tutor so that the individual becomes an independent person and knows his environment. There is an imbalance in the number of ratios between BK teachers and students who are mentored and there are still many BK teachers who do not meet the educational qualifications in accordance with their fields, which need to be addressed immediately. This research uses a descriptive qualitative research approach, with the type of case study. Data collection methods by interview, observation and documentation. While this research data analysis uses data reduction, data display and conclusion drawing. The results showed that the counseling guidance process at MA Raudlatut Thalabah took the form of personal guidance, social guidance, study guidance and career guidance. In addition counseling services in the form of orientation services, information services, distribution and placement services, content mastery services, individual counseling services, group guidance services, group counseling services, consulting services and mediation services. The guidance and service activities are supported by activities in the form of instrumentation applications, data sets, case conferences, case handover, home visits and literature display.